Garbarata sebagai Media Iklan Strategis: Studi Peningkatan Minat Perusahaan di Bandar Udara Internasional Minangkabau Padang - Rafli Aditya R; Novan Muhammad Saofi A2; Elfi Amir; 1Politeknik Penerbangan Indonesia Curug (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
This study explores the strategic use of garbarata as an advertising medium at Minangkabau International Airport, Padang. The garbarata, which is a connecting bridge between the terminal and the aircraft, has great potential as an exclusive advertising space and has high exposure to passengers. However, this potential has not been optimally maximized. This study uses a qualitative approach with a case study method. Data collection was conducted through in-depth interviews with airport management, direct observation of the garbarata conditions, and analysis of documentation related to advertising policies and non-aeronautical asset management. The results of the study indicate that there are several main obstacles in the use of garbarata as a promotional medium. These obstacles include minimal promotional activities to potential advertisers, unclear pricing systems for advertising space rentals, lack of collaboration with advertising agencies, and limitations in the provision of design services and visual creativity. This has led to low interest of companies in utilizing this media as part of their marketing strategy. To overcome these problems, this study proposes several development strategies, including: increasing active and planned promotional activities, setting flexible and competitive rental prices, strategic collaboration with professional advertising agencies, and providing creative design services to support the effectiveness of advertising messages. This strategy is expected to attract more companies to advertise on the aerobridge, thereby increasing the airport's non-aeronautical revenue. With proper optimization, the aerobridge will not only serve as a functional passenger facility but can also transform into a strategic asset supporting the airport's sustainable commercial development and creating added value for both the operator and its business partners.